2012
DOI: 10.1007/s10562-012-0869-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Ga2O3 Clusters on Zeolite ZSM-5 for the Conversion of Methanol to Aromatics

Abstract: Composites of Ga 2 O 3 clusters and zeolite ZSM-5 were evaluated for the transformation of methanol to hydrocarbons. Comparison of the activity with ZSM-5 showed that the Ga 2 O 3 clusters are responsible for the enhanced selectivity to aromatics via contact synergy, thus showing the importance of non framework gallium species for this reaction. TEM analysis of fresh and spent catalysts allowed the identification of the formation of carbonaceous products at the Ga 2 O 3 /zeolite interface region, and this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 36 publications
0
76
0
Order By: Relevance
“…1 The dope of metal on ZSM-5 improved the dehydrogenation activity of the catalyst and, consequently, increased the yield of aromatics. [2][3][4][5][6][7][8][9][10][11][12][13] As a result, the weight ratio of aromatics in liquid organic product in methanol to aromatics (MTA) process was around 90%, which is far higher than that(about 35%) in methanol to gasoline (MTG) process and that (50-65%) in catalytic reforming of naphtha. [1][2][3][4][5][6][7][8][9][10][11][12][13] In addition, the selectivity to para-xylene (PX) in xylene (X) in the MTA product is 23-24%, which is higher than that (around 18%) from the catalytic reforming of naphtha.…”
Section: Introductionmentioning
confidence: 98%
“…1 The dope of metal on ZSM-5 improved the dehydrogenation activity of the catalyst and, consequently, increased the yield of aromatics. [2][3][4][5][6][7][8][9][10][11][12][13] As a result, the weight ratio of aromatics in liquid organic product in methanol to aromatics (MTA) process was around 90%, which is far higher than that(about 35%) in methanol to gasoline (MTG) process and that (50-65%) in catalytic reforming of naphtha. [1][2][3][4][5][6][7][8][9][10][11][12][13] In addition, the selectivity to para-xylene (PX) in xylene (X) in the MTA product is 23-24%, which is higher than that (around 18%) from the catalytic reforming of naphtha.…”
Section: Introductionmentioning
confidence: 98%
“…Reducing the aromatic content in the produced fuels is very important to http address the global more strict environmental regulations. In the past few years, more continuous researches were reported on the modification of HZSM-5 by various metal oxide composites, such as CuO [21], ZnO/CuO [8] and Ga 2 O 3 [22,23], as well as acid or alkali treatment [2,24] in MTG process. Most studies revealed that the acidic properties and mesopore formation of ZSM-5 catalysts were well altered, and the diffusion properties of the pore channels were improved.…”
Section: Introductionmentioning
confidence: 99%
“…Both MTG and MTA, but especially MTA, research has mainly focused on modified MFI‐type catalysts . Investigations on modifying the zeolite with metal oxides such as Cu, Ni, Ag,, Ga, or Zn, agree that addition of these oxides provides further acid or basic sites to the zeolite materials resulting in increased activity and selectivity towards the aromatic products. For example, Inoue et al .…”
Section: Methanol To Aromaticsmentioning
confidence: 99%